Transformation of Learning in the Digital Era: Opportunities and Challenges of Social Media in the Merdeka Curriculum for Management Students (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
Learning transformation in the digital era presents new opportunities and challenges for higher education in Indonesia, particularly in the implementation of the Merdeka Curriculum in management study programs. This study aims to identify the opportunities, challenges, and impacts of utilizing social media platforms, including WhatsApp, Instagram, Facebook, YouTube, and TikTok, in the Merdeka Curriculum-based learning process. The methodology employed is a Systematic Literature Review (SLR) of nine scientific articles published between 2019 and 2024, which are relevant to the topic of digital transformation and social media in management education. The research findings indicate a very high level of social media adoption among students, opening up significant opportunities for collaborative learning, the development of soft skills and digital skills, and project-based contextual learning. However, significant challenges also emerged, such as the digital infrastructure gap, uneven digital literacy, privacy issues, data security, and the potential for distraction from non-academic content. Effective social media integration has been proven to increase learning motivation, academic participation, and work readiness of management students when supported by clear institutional policies and ongoing training. This research recommends the need for strategies to strengthen digital infrastructure, digital literacy, and adaptive ethical policies to ensure that digital transformation in higher education is optimal and inclusive.
Keywords: digital transformation; social media; digital learning; Merdeka Curriculum; management students